Localization of full-length recombinant human proteoglycan-4 in commercial contact lenses using confocal microscopy. Issue 1 (2nd January 2020) - Cheung, Steven; Subbaraman, Lakshman N.; Ngo, William; Jay, Gregory D.; Schmidt, Tannin A.; Jones, Lyndon
Abstract: The aim of this study was to determine the sorption location of full-length recombinant human proteoglycan 4 (rhPRG4) tagged with fluorescein isothiocyanate (FITC) to four silicone hydrogel contact lenses [balafilcon A (PureVision, Bausch + Lomb), senofilcon A (Acuvue Oasys, Johnson & Johnson), comfilcon A (Biofinity, CooperVision), lotrafilcon B (Air Optix, Alcon)] and one conventional hydrogel lens [etafilcon A (Acuvue 2, Johnson & Johnson)], using confocal laser scanning microscopy (CLSM). Lenses ( n  = 3 each) were incubated under two conditions: (1) FITC-rhPRG4 solution at 300 μg/mL and (2) phosphate-buffered saline, for 1 h at 37 °C in darkness with gentle shaking. The central 4 mm of each lens was removed and viewed with the Zeiss 510 CLSM using an argon laser at 488 nm (FITC excitation 495 nm, emission 521 nm). Depth scans were taken at 1 μm intervals to a maximum depth of 100 μm. All lens materials demonstrated sorption of rhPRG4. Both senofilcon A and balafilcon A revealed FITC-rhPRG4 penetration into the bulk of the lens, generally favoring the surface. rhPRG4 was observed exclusively on the surface of lotrafilcon B, with no presence within the bulk of the lens. rhPRG4 was evenly distributed throughout the bulk of the lens, as well as on the surface, for comfilcon A and etafilcon A. The sorption profile of FITC-rhPRG4 was successfully visualized using CLSM in various contact lens materials. The polymer composition, surface treatment and pore size of the material can influence the sorption of rhPRG4.